Induced Regulatory T Cells Superimpose Their Suppressive Capacity with Effector T Cells in Lymph Nodes via Antigen-Specific S1p1-Dependent Egress Blockage - Geng, Shuang; Zhong, Yiwei; Zhou, Xiaoyu; Zhao, Gan; Xie, Xiaoping; Pei, Yechun; Liu, Hu; Zhang, Huiyuan; Shi, Yan; Wang, Bin (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) restrict overexuberant lymphocyte activation. While close proximity between Tregs and their suppression targets is important for optimal inhibition, and literature indicates that draining lymph nodes (LNs) may serve as a prime location for the suppression, signaling details orchestrating this event are not fully characterized. Using a protocol to enable peripheral generation of inducible antigen-specific Tregs (asTregs) to control allergen-induced asthma, we have identified an antigen-specific mechanism that locks asTregs within hilar LNs which in turn suppresses airway inflammation. The suppressive asTregs, upon antigen stimulation in the LN, downregulate sphingosine-1-phosphate receptor 1 egress receptor expression. These asTregs in turn mediate the downregulation of the same receptor on incoming effector T cells. Therefore, asTregs and effector T cells are locked in these draining LNs for prolonged interactions. Disruption of individual steps of this retention sequence abolishes the inflammation controlled by asTregs. Collectively, this study identifies a new requirement of spatial congregation with their suppression targets essential for asTreg functions and suggests therapeutic programs via Treg traffic control.